ANALISIS PENGARUH PERTUMBUHAN EKONOMI, PERTUMBUHAN PENDUDUK DAN INFLASI TERHADAP TINGKAT KEMISKINAN DI JAWA TIMUR TAHUN 2004-2014 - Hambarsari, Dwi Puspa; Inggit, Kunto (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2016)
Poverty is inability toÂ minimum standards basic needs which includes some food and non food. Proverty in East Java is one of social problems are more attention from the government of east java. This research aims to analyze the factors affect poverty level of East Java. Variabel is used includes economic growth, population growth and inflation. This research using secondary data obtained from the central bureau of statistics in East Java. Secondary data used in this research in the form of time series the period 2004- 2014. This research uses the method of analysis linear regression multiple with program assistance spss 21. Based on the results of multiple linear regression analysis obtained the following conclusions: variable of economic growth and a significant negative effect on poverty levels in East Java because the result is smaller than the significance level of significance (Î± = 0.05) in the amount of population and inflation 0,010.Pertumbuhan no effect a significant changed in poverty in East Java as the result of greater significance than the level of significance (Î± = 0.05) in. While for R2 obtained yield was 0.678 or 67.8 %, this means that the poverty rate in East Java explained by the three independent variables for 67.8 % and 32.2 partially explained by other factors beyond the study models .Key words: The level of poverty in East Java, Economic Growth, Population Growth and Inflation.